Respuestas

2012-04-16T06:33:13+02:00

m+n=1  

 

elevamos al cuadrado cada mienbro de la ecuacion:

 

(m+n)2=12               m+n=1                                                      m3+n3+3(m+n)mn=1

 

m2 +2mn+n2 =1        elevando al cubo ambos mienbros              m3+n3+3(1)mn=1

 

m2+n2=1-2mn          (m+n)3=13                                                 m3+n3=1-3mn

 

 

remplazando:

 

 

A=3(1-2mn)-2(1-3mn)

 

A=3(1)-3(2mn) - 2(1) -2(-3m)

 

A=3-6mn-2+6m

 

A=3-2

A=1

 

 

DE AHI TE PASO LAS OTRAS DOS